Bibliometric Analysis of the Radio Da'wah Research - Ismandianto, Ismandianto; Sazali, Hasan; Sikumbang, Ahmad Tamrin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to understand the research trends in radio da'wah, identify relationships between scientific concepts, and determine the radio da'wah science network based on keywords and author collaboration. The method used in this research is descriptive bibliometric analysis, and the data used was taken from 2013-2023. Data was collected from the Scopus and Google Scholar databases with the keyword da'wah radio. Data collection was carried out using Publish or Perish software as metadata. Data analysis was carried out using Vosviewer software as a bibliometric analysis medium. The research results show that da'wah radio publications experience fluctuating development, with Scopus publications being very low. Meanwhile, publications in nationally accredited journals and national journals have increased significantly. From the visualization Vosviewer, it can be seen that Islamic institutions or universities dominate research on radio da'wah.